Autoethnography in Intrapersonal and Intra-Active Training of Pedagogues. Selected Aspects and Application Possibilities - Ciechowska, Magdalena; Kusztal, Justyna; Szymańska, Maria (Przegląd Badań Edukacyjnych (Educational Studies Review), 2019)
The article presents autoethnography in the context of posthumanistic student education as a way not only for a deep self-knowledge, but also for understanding other people. In this context, the authors seek answers to questions about the essence of autoethnography as a research method and its significance for personalized intra-personal and intra-active pedagogical training. By pedagogues/educators we mean people who lead others to maturity. The article presents innovative research techniques conducive to auto-ethnographic cognition and examples of application of autoethnography in the education of pedagogical students.